Organisational commitment among academic staff of a private university - Jayachandran, Karuppusamy (2019)
The main purpose of this research is to investigate the determinants of organizational commitment among academic staff of private universities. Specifically, the objective of this study is to examine the relationships between organizational commitment, job commitment, job satisfaction and perceived organizational support. Questionnaires were distributed among academic staff in a private university located in Semeling, Kedah through Google Forms and printed version of the questionnaire. All the data were analyzed by using Statistical Package for Social Science (SPSS) version 25.0. Two types of data analysis were used, which are descriptive analysis and inferential analysis. Descriptive analysis is used to study the respondent demographic information such as gender, age, race, nationality, level of education, length of services, monthly income level, current position and status of employment. The inferential analysis is used to determine the relationships between dependent variable which is organizational commitment and independent variables such as job commitment, job satisfaction and perceived organizational support. The results of the study show that the relationship between organizational commitment and the three independent variables which are job satisfaction, job involvement and perceived organizational support has positive relationship among the academic staff of a private university. Accordingly, based on the multiple regression analysis, the study found that one independent variable which is job involvement has no significant relationship with organizational commitment while job satisfaction and perceived organizational support has significant relationship with organizational commitment